Determining ACE-2 Level and Some Relevant Biochemical Parameters and studying the effect of Gender in Iraqi Diabetic Patients with Glomeruli and Renal Tubules Fibrosis as Early Prediction Marker - Reham Khuldon Ibrahim; Kadhim K. Ghudhaib; Ali Abdulmajid Dyab Allawi (مجلة بغداد للعلوم)
Diabetic kidney disease is an illness of the glomerulus that interferes with the glomerular filtration barrier (GFB), which is worked to enable kidney to selective purification of water and solutes in addition to limiting the movement of large macromolecules such as albumin. In the glomerular endothelium, mesangial cells, foot cells, and the brush border of the proximal tubules, ACE-2 is expressed and that the kidneys represent the highest-expressing region of this enzyme. Thus, the current study aimed to evaluate ACE-2 level in this case compared to healthy condition. The study Conducted with 120 male and female ranging in age (30-65) years old. Ninety patients with type 2 diabetes subdivided into three groups on the basis of ACR criteria including normoalbuminuria, microalbuminuria, macroalbuminuria (30 patients for each group) and 30 healthy people served as the control group, all visited Baghdad Teaching Hospital / Medical City and Al-Yarmouk Teaching Hospital, at the period between December 2021 and May 2022.  ACE-2 levels were determined using the ELISA technique. Urea results showed significant differences between diabetic nephropathy in patient and control group in female cases but no significant differences in male patients with diabetic nephropathy and control group. Similar results were obtained in K ion. Also the results revealed significant differences in Na ion, ACR, eGFR, Urea, FBS, creatinine between diabetic nephropathy groups and healthy group.ACE-2 represents a good marker for early prediction in diabetic nephropathy case. ROC data analysis support the importance of ACE-2 in diagnosis of the studied disease case.